2002
DOI: 10.1111/j.1545-5300.2002.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

The Families and Democracy Project

Abstract: The Families and Democracy Project moves family therapists and other professionals into the community via a critique of traditional provider/consumer models of family services, a set of principles about the civic engagement of families in partnership with professionals, and a set of public practices for working on community problems. We describe the Families and Democracy model and three specific projects. We distinguish the model from traditional hierarchical and collaborative models of working with families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…Putnam (2000) notes that an individual's well-being is strongly related to the quality of social support in his or her life. Doherty and Carroll (2002) state, ''Families must be engaged as producers and contributors to their communities, and not just as clients or consumers of services'' (p. 583). Instead of passively receiving services from the community, clients work to improve the environment in which they live.…”
Section: Questions To Extend the Story Into The Futurementioning
confidence: 99%
“…Putnam (2000) notes that an individual's well-being is strongly related to the quality of social support in his or her life. Doherty and Carroll (2002) state, ''Families must be engaged as producers and contributors to their communities, and not just as clients or consumers of services'' (p. 583). Instead of passively receiving services from the community, clients work to improve the environment in which they live.…”
Section: Questions To Extend the Story Into The Futurementioning
confidence: 99%
“…The FFP was a federally and state funded demonstration project formed in response to the call for extending marriage education to fragile families. The FFP was uniquely designed using principles from the Families and Democracy model (Doherty & Carroll, 2002) in partnership between university researchers and community leaders. It took shape as an intense, in-home education and support program.…”
Section: Design Of the Family Formation Projectmentioning
confidence: 99%
“…This case prompts a larger question of the role of family in community mobilization and civic action. Some recent community building initiatives have placed the impetus of community change and civic engagement on the family unit (Doherty & Carroll, 2002; Erickson & Louv, 2002; Rojano, 2004). Research has shown that parents who are more active in raising their children are more likely to exhibit higher levels of civic engagement (e.g., Wilcox, 2002).…”
mentioning
confidence: 99%